2003
DOI: 10.1002/jcp.10415
|View full text |Cite
|
Sign up to set email alerts
|

Normal skin wound and hypertrophic scar myofibroblasts have differential responses to apoptotic inductors

Abstract: During wound healing, myofibroblasts play a central role in matrix formation and wound contraction. At the end of healing, there is evidence that myofibroblasts disappear via apoptotic pathways. Hypertrophic scars are a fibroproliferative disorder that leads to considerable morbidity. It has been postulated that a defect in myofibroblast apoptosis could be responsible for the pathological scar formation, but no evidence exists. We have isolated and cultured human normal wound (Wmyo) and hypertrophic scar (Hmyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
2
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 27 publications
4
104
2
6
Order By: Relevance
“…However, we believe that the emergence of an apoptosis-resistant phenotype of AMCs may represent one plausible mechanism for "nonresolution" of the repair phase of ARDS. Apoptosis is a well-defined physiological process for normal tissue remodeling events in embryonic development and in the decreased cellularity that accompanies resolution of cutaneous wound healing (19,44). Furthermore, a previous study by our group demonstrated enhanced activation of Akt and focal adhesion kinase in fibrotic regions of the lung in a murine model of bleomycin-induced injury and fibrosis; systemic administration of a protein kinase inhibitor that targets these prosurvival protein kinases diminished the accumulation of myofibroblasts and attenuated fibrotic tissue responses (54).…”
Section: Discussionmentioning
confidence: 99%
“…However, we believe that the emergence of an apoptosis-resistant phenotype of AMCs may represent one plausible mechanism for "nonresolution" of the repair phase of ARDS. Apoptosis is a well-defined physiological process for normal tissue remodeling events in embryonic development and in the decreased cellularity that accompanies resolution of cutaneous wound healing (19,44). Furthermore, a previous study by our group demonstrated enhanced activation of Akt and focal adhesion kinase in fibrotic regions of the lung in a murine model of bleomycin-induced injury and fibrosis; systemic administration of a protein kinase inhibitor that targets these prosurvival protein kinases diminished the accumulation of myofibroblasts and attenuated fibrotic tissue responses (54).…”
Section: Discussionmentioning
confidence: 99%
“…1). In hypertrophic scars, the presence of apoptosis-resistant myofibroblasts high in antiapoptotic protein Bcl-2 has been reported (256). Although the mechanisms remain unclear, TGF-␤ may induce myofibroblast resistance to apoptosis (138).…”
Section: Chronic Fibrosis and Cancer Differ From Transient Wound Healmentioning
confidence: 99%
“…MFs also cause wound contraction and undergo apoptosis. However, in the last stage of wound healing, a defect in the apoptosis of MF and the persistence of MF results in an hypertrophic scar tissue [42] . A tumorigenic process involves acquiring multiple genetic mutations.…”
Section: Functional Similarities and Differences Between Wound Healinmentioning
confidence: 99%